Development of ABEL KERINDO Interactive Multimedia based on Articulate Storyline to Learn Social Science for Alpha Generation Students in Elementary School - Divandari Setya Putri; Farid Ahmadi (Sekolah Dasar: Kajian Teori dan Praktik Pendidikan, 2024)
Minimizing the use of technology-based interactive multimedia in social science learning reduces the interest and learning outcomes of alpha-generation students. Research and development (R&D) design with a waterfall development model, which includes requirements, design, Implementation, verification, and maintenance phases, is used in this research. Developing interactive multimedia product ABEL KERINDO "Ayo Belajar Kerajaan di Indonesia" based on Articulate Storyline to probe its eligibility and effectivity becomes the purpose of this research. From the validation results, this product is considered highly qualified, with a material expert rating of 96.25 percent, a media expert of 93.75 percent, teacher 100 percent, and student participant 98 percent, which yields an average score of 97%. This multimedia can significantly improve the learning outcome for fourth-grade students of SD Kanisius Beringin Semarang, with the difference between the pretest-posttest ratio of 23.75 and the N-gain ratio of 0.545, which belongs to moderate criteria. Students' interest in learning also increased from 66 percent to 80 percent, indicating the product's effectiveness in increasing engagement and learning outcomes. Overall, the product can be considered highly eligible and effective for enhancing the interest and learning outcomes of alpha-generation students.